Does social capital interact with economic hardships in influencing older adults' health? A study from China - Lijuan Gu; Yang Cheng; David R. Phillips; Mark Rosenberg; Linsheng Yang; Li Wang; Hairong Li (BMC, 2021)
Abstract Background The importance of social and economic capital as predictors of health is widely documented, yet the complexity of interactions between them and effects on older people's health is still unclear. Combining the material and psychosocial explanations of health, this study explores the potential interactions between social and economic capital in influencing older adults' health in urban and rural China. Methods Using data from the China Family Panel Survey, physical and mental health in 2018 were regressed on social and economic capital indicators in 2016, controlling for sociodemographic characteristics of 3535 respondents aged 65 and older. Rothman's synergy index was calculated to investigate potential interaction effects. Results Economic hardships were significantly related to both self-reported health and mental health. Neighborhood cohesion and social participation were significantly associated with mental health for all, bonding trust was significantly associated with mental health for urban older people. We found no significant associations between social capital components and self-reported health. There was an interaction effect between low neighborhood cohesion and economic hardships, and between low social participation and economic hardships, creating an increased burden of poor mental health. The interaction effect between low bonding trust and economic hardships on mental health was apparent only among urban older people. Conclusions Geographical settings are important factors in the complexity between social and economic capital in affecting older health. Intervention efforts directed towards reducing simultaneously multiple dimensions of deprivation, such as poverty, social exclusion, social isolation, could be helpful in improving older people's health. In materially deprived places, policies to promote health equity by improving social capital but without eliminating poverty may be less effective.